MpFEW RHIZOIDS1 miRNA-mediated lateral inhibition controls rhizoid cell patterning in Marchantia polymorpha - Thamm, A; Saunders, TE; Dolan, L (Cell Press, 2020)
Lateral inhibition patterns differentiated cell types among equivalent cells during development in bacteria, metazoans, and plants. Tip-growing rhizoid cells develop among flat epidermal cells in the epidermis of the early-diverging land plant Marchantia polymorpha. We show that the majority of rhizoid cells develop individually, but some develop in linear, one-dimensional groups (chains) of between 2 and 7 rhizoid cells in wild-type plants. The distribution of rhizoid cells can be accounted for within a simple cellular automata model of lateral inhibition. The model predicted that in the absence of lateral inhibition, two-dimensional rhizoid cell groups (clusters) form. These can be larger than those formed with lateral inhibition. M. polymorpha rhizoid differentiation is positively regulated by the ROOT HAIR DEFECTIVE SIX-LIKE1 (MpRSL1) basic-helix-loop-helix (bHLH) transcription factor, which is directly repressed by the FEW RHIZOIDS1 (MpFRH1) microRNA (miRNA). To test if MpFRH1 miRNA acts during lateral inhibition, we generated loss-of-function (lof) mutants without the MpFRH1 miRNA. Two-dimensional clusters of rhizoids develop in Mpfrh1lof mutants as predicted by the model for plants that lack lateral inhibition. Furthermore, two-dimensional clusters of up to 9 rhizoid cells developed in the Mpfrh1lof mutants compared to a maximum number of 7 observed in wild-type groups. The higher steady-state levels of MpRSL1 mRNA in Mpfrh1lof mutants indicate that MpFRH1-mediated lateral inhibition involves the repression of MpRSL1 activity. Together, the modeling and genetic data indicate that MpFRH1 miRNA mediates lateral inhibition by repressing MpRSL1 during pattern formation in the M. polymorpha epidermis.